1973
DOI: 10.1002/jbm.820070327
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro changes in strength of orthopedic calcium aluminates

Abstract: SummaryCalcium aluminate bars were formulated to study the effect of real and simulated biological environments on strength. Static fatigue tests revealed that the strength of these potential internal bone prostheses decreased to ca. 60% of their initial strength after less than 100 min while being held at constant stress in solution. Calcium aluminate bars aged for 12 weeks in water or Ringer solution were also found to exhibit large losses in strength, while bars implanted in vivo for the same period of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The in vitro aging was performed as previously described by Schnittgrund et al [9], by placing rods in jars containing Ringer's solution. They were allowed to soak for 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro aging was performed as previously described by Schnittgrund et al [9], by placing rods in jars containing Ringer's solution. They were allowed to soak for 1.…”
Section: Methodsmentioning
confidence: 99%
“…Schnittgrund et al [9] showed losses of 40% within 100 min when calcium aluminate bars were aged under conditions of static loading and 10% when aged in vivo for 3 months. In contrast were the studies of glassy carbon which failed t o show any statistically significant losses of flexural strength in the in vivo aging studies and which were shown to be comparatively resistant to static fatigue [lo].…”
Section: Introdu Ctl Onmentioning
confidence: 97%
“…The implants were made from porous ceramics produced as described by Lyng et al (1973 Frakes et al (1974) and Schnittgrund et al (1973) indicate that the strength of alumina may deteriorate due to stress corrosion both in vivo and in uitro. However, according to Schnittgrund e t al.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve this goal, a lot of methods and devices have been proposed such as guided tissue regeneration, bone graft, and application of growth factors [1]. Past studies have shown that calcium aluminate has excellent biocompatibility [2], host adaptability and mineralization capacity [3], which facilitates hard and soft tissue reconstruction [4]. However, in order to use calcium aluminate cement clinically as a bony cement, the conventional setting time(about 7 hours) needs to be shortened to below 60 minutes.…”
Section: Introductionmentioning
confidence: 99%